Formation and Reactivity of the Terminal Vanadium Nitride Functionality12. Issue 22 (22nd May 2013) - Tran, Ba L.; Krzystek, J.; Ozarowski, Andrew; Chen, Chung‐Hsing; Pink, Maren; Karty, Jonathan A.; Telser, Joshua; Meyer, Karsten; Mindiola, Daniel J.
Abstract: The transformation of vanadium(III) azides, [(nacnac)V(N3 )(X)] n nacnac = [ArNC(CH3 )]2 CH –, Ar = 2, 6‐(CHMe2 )2 C6 H3 ; X = Ntol2 –, where tol = 4‐MeC6 H4, n = 1; X = ArO –, n = 2, to their corresponding vanadium(V) nitrides, [(nacnac)V≡N(X)], was investigated through an isotopic labeling crossover experiment. The nuclearity of the azide species is dependent on the size of the supporting ligand, X, with X = ArO –, thus featuring a V2 N6 core with two μ2 ‐1, 3‐N3 bridging ligands across the V III centers. SQUID magnetization studies and multifrequency, high‐field EPR (HFEPR) experiments reveal the mononuclear azide complex to be consistent with an S = 1 system, while the dimeric azide system is weakly antiferromagnetically coupled with a spin singlet ground state and thermally accessible triplet and quintet states. These combined results suggest that the transformation of a vanadium(III) azide to a vanadium(V) nitride most likely occurs by a bimetallic mechanism, where Lewis bases inhibit N2 extrusion. Room‐temperature generation of the nitride products from their corresponding azides can also be accomplished stoichiometrically with a Lewis acid, such as B(C6 F5 )3, and catalytically, through an unsaturated vanadium(II) fragment, [(nacnac)V(Ntol2 )]. Abstract : The transformation of V III azides to the corresponding V V nitrides was investigated through isotopic labeling crossover experiments, SQUID magnetization, and multifrequency/high‐field EPR studies. While Lewis bases inhibit the azide‐to‐nitride transformation, nitride complexes are formed by a bimetallic mechanism. Stoichiometric Lewis acid and catalytic amount of V II complex also rendered azide‐to‐nitride formation. However, Lewis bases inhibit formation of nitride product.